Risk of long-term care admissions among Medicare beneficiaries treated with pimavanserin or quetiapine for Parkinson's disease psychosis in USA: a retrospective administrative claims database analysis - Krithika Rajagopalan; Nazia Rashid; Dilesh Doshi (Becaris Publishing Limited, 2023)
Aim: Risk of long-term care (LTC) admission (LTCA) associated with atypical antipsychotic (AAP) use among patients with Parkinson's disease psychosis (PDP) is a major concern. However, no comparative studies have examined the differences in risk of LTC admissions between pimavanserin (PIM), the only FDA approved AAP for PDP, and other off-label AAPs including quetiapine (QUE). Objective: To examine all cause LTCA rates and risk among PDP patients treated with AAPs such as QUE or PIM. Methods: Analysis of Parts A, B and D claims (100% Medicare sample; 2013-2019) of Medicare beneficiaries with PDP that initiate ≥12-month continuous PIM or QUE monotherapy from 1 January 2014 to 31 December 2018 (i.e., index date) without any AAP use in the 12-month pre-index period was conducted. Outcome assessments among 1:1 propensity score-matched (31 variables - age, sex, race, region and 27 Elixhauser comorbidities) beneficiaries on PIM versus QUE included risk of all-cause skilled nursing facility stays (SNF-stays), LTCstays, and overall LTCA (i.e., SNF-stays or LTC-stays). All-cause LTCA rates and LTCA risk were compared using logistic regression and cox proportional hazards models, respectively, controlling for demographics, comorbidities and co-existing-dementia or insomnia. Results: Of the matched sample (n = 842 for each group) from total sample (n = 9652), overall all-cause LTCA and SNF-stay rates were 23.2 and 20.2% for PIM versus 33.8 and 31.4% for QUE, respectively (p < 0.05, for each). Hazard ratio (95% CI) for risk of SNF-stay and overall LTCA was 0.78 (0.61, 0.98) and 0.80 (0.66, 0.97), respectively, for PIM versus QUE beneficiaries (p < 0.05, for each). Conclusion: The 20% lower risk of LTCA (i.e., greater delay) with PIM versus QUE in this analysis may suggest that PIM should be started early for the treatment of PDP.